The in vitro assessment of a novel vaping technology. (2020) - Breheny, D.; Thorne, D.; Baxter, A.; Bozhilova, S.; Jaunky, T.; Santopietro, S.; Taylor, M.; Terry, A.; Gaça, M.
Graphical abstract: Abstract: We have developed a novel vaping product (NVP) IS1.0(TT), which utilises a stainless-steel mesh to transfer and vaporise the e-liquid, mitigating some of the potential sources of toxicants that can be generated using the more traditional 'wick and coil' approach. The emissions from IS1.0(TT) have previously been found to have lower levels of toxicants overall when directly compared with a commercial wick and coil e-cig. This current study assessed the toxicological responses to aerosols from this NVP. Responses induced by IS1.0(TT)were compared to those from a 3R4F reference cigarette, using in vitro test methods which included regulatory genetic toxicological assays as well as some more contemporary screening approaches. The experimental conditions were designed to facilitate the testing of aerosol from this vaping product at doses that in most cases greatly exceeded those of the 3R4F comparator showed little to no toxicological responses and demonstrated significantly reduced effects in these in vitro assays when compared to 3R4F. Furthermore, the extreme doses tested in the present study indicate that the toxicant profile of this NVP translates to lower biological activity in vitro, and suggests that the absolute risk hazard level associated with electronic cigarettes can be reduced through continuous improvement as the technology evolves.